Face Patch Resting State Networks Link Face Processing to Social Cognition - Schwiedrzik, Caspar M.; Zarco, Wilbert; Everling, Stefan; Freiwald, Winrich A. (PLOS Biology, 2015)
An analysis of the functional connectivity of regions of the monkey brain involved in face recognition suggests substrates for the cognitive, mnemonic, emotive, and motoric impact of faces, revealing striking similarities to the human brain, and implying a deep evolutionary heritage of even the most high-level sociocognitive functions.